Effects of a community‐oriented obesity prevention programme on indicators of body fatness in preschool and primary school children. Main results from the IDEFICS study. (December 2015) - De Henauw, S.; Huybrechts, I.; De Bourdeaudhuij, I.; Bammann, K.; Barba, G.; Lissner, L.; Mårild, S.; Molnár, D.; Moreno, L. A.; Pigeot, I.; Tornaritis, M.; Veidebaum, T.; et al.
Summary: Background/Objectives: Childhood obesity is a major public health concern but evidence‐based approaches to tackle this epidemic sustainably are still lacking. The Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS (IDEFICS) study investigated the aetiology of childhood obesity and developed a primary prevention programme. Here, we report on the effects of the IDEFICS intervention on indicators of body fatness. Subjects/Methods: The intervention modules addressed the community, school and parental level, focusing on diet, physical activity and stress‐related lifestyle factors. A cohort of 16, 228 children aged 2–9.9 years – about 2000 per country – was equally divided over intervention and control regions. (Participating countries were Sweden, Germany, Estonia, Hungary, Cyprus, Italy, Spain and Belgium.) We compared the prevalence of overweight/obesity and mean values of body mass index z ‐score, per cent body fat and waist‐to‐height ratio over 2 years of follow‐up. Mixed models adjusting for age and socioeconomic status of the parents and with an additional random effect for country accounted for the clustered study design. Results: The prevalence of overweight and obesity increased in both the intervention and control group from 18.0% at baseline to 22.9% at follow‐up in the control group and from 19.0% to 23.6% in the intervention group. The difference in changes between control and intervention was not statistically significant. For the cohort as a whole, the changes in indicators of body fatness did not show any clinically relevant differences between the intervention and control groups. Changes in favour of intervention treatment in some indicators were counterbalanced by changes in favour of the control group in some other indicators. Conclusions: Over the 2‐year‐observation period, the IDEFICS primary prevention programme for childhood obesity has not been successful in reducing the prevalence of overweight and obesity nor in improving indicators of body fatness in the target population as a whole.